Identification of circulating microRNAs for the differential diagnosis of Parkinson's disease and Multiple System Atrophy - Vallelunga, Annamaria; Ragusa, Marco; Di Mauro, Stefania; Iannitti, Tommaso; Pilleri, Manuela; Biundo, Roberta; Weis, Luca; Di Pietro, Cinzia; De Iuliis, Angela; Nicoletti, Alessandra; Zappia, Mario; Purrello, Michele; et al. (Frontiers in Cellular Neuroscience, 2014)
Background. Parkinson's disease (PD) is a progressive neurodegenerative disorder which may be misdiagnosed with atypical conditions such as Multiple System Atrophy (MSA), due to overlapping clinical features. MicroRNAs (miRNAs) are small noncoding RNAs with a key role in post-transcriptional gene regulation. We hypothesized that identification of a distinct set of circulating miRNAs (cmiRNAs) could distinguish patients affected by PD from MSA and healthy individuals. Results. Using TaqMan Low Density Array technology, we analysed 754 miRNAs and found 9 cmiRNAs differentially expressed in PD and MSA patients compared to healthy controls. We also validated a set of 4 differentially expressed cmiRNAs in PD and MSA patients versus controls. More specifically, miR-339-5p was downregulated, whereas miR-223*, miR-324-3p and mir-24 were upregulated in both diseases. We found cmiRNAs specifically deregulated in PD (downregulation of miR-30c and miR-148b) and in MSA (upregulation of miR-148b). Finally, comparing MSA and PD, we identified 3 upregulated cmiRNAs in MSA serum (miR-24, miR-34b, miR-148b). Conclusions. Our results suggest that cmiRNA signatures discriminate PD from MSA patients and healthy controls and may be considered specific, non-invasive biomarkers for differential diagnosis.